Beginning the Linux Command Line - Vugt, Sander van (Apress, 2012)
This book is for anyone who wants to master Linux from the command line. When writing it, I had in mind system administrators, software developers, and enthusiastic users who want to get things going from the Linux command line. For beginning users, this may be a daunting task, as Linux commands often have many options documented only in ...... pages that are not that easy to understand. This book is distribution agnostic. That is, while writing it, I’ve checked all items against Ubuntu, Red Hat, and SUSE. Since most distributions are quite similar to one of these three, this book should help you with other distributions as well. There is only one item in the book that is not distribution agnostic: the Appendix, which explains how to install OpenSUSE. I’ve chosen to cover installation of just one distribution, because if you don’t have any Linux installed yet, you probably don’t care what you install. If you do care what distribution to work with, you probably have it installed already.